From Functional Family to Spinster Sisters: Australia's Distinctive Path to Relationship Recognition - Reg Graycar; Jenni Millbank (Washington University Journal of Law & Policy, 2007)
This Essay reflects on the approaches that Australia, and to a lesser extent New Zealand, have taken to relationship recognition, focusing in particular on the ways in which they have differed profoundly from what has happened in the United States. Specifically, the relationship recognition debate in Australia through the 1990s was characterized by the absence of any real interest in marriage and instead focused on developing more functional and adaptive models of relationship recognition, primarily through presumption-based models (for example, the ascription of relationship status). In this discussion we start, by way of background, with an explanation of the development of widespread legal recognition of heterosexual non-marital cohabiting relationships (“de facto relationships”) in Australia. We then briefly outline the first same-sex relationship law reforms in Australia in 1999 in the state of New South Wales before touching on areas of similarity and difference in other Australian states and territories. We then critically analyze this history, highlighting the features that are distinctive to Australia, such as the emphasis on presumptive recognition, the move to recognize non-couple relationships, and, until recently, the lack of focus on marriage. Since 2004, marriage has come to be an increasingly popular equality goal in Australia and we consider possible reasons for this. We also examine the ways in which the open-ended “interdependency” relationship model, originally promoted by progressive functional family advocates has, arguably, been co-opted and subverted by conservatives. We conclude with some reflections on how these very different approaches might be explained.
Keywords: Same-sex marriage – Australia; Unmarried couples – Australia; Domestic relations law reform; Comparative law; Domestic relations; Marriage law; Same-sex marriage; Australia; New Zealand; United States